Author Identification for Telugu Classical Poems - Pandian, A.; V.Ramalingam, V.; Manikandan, K.; Jeevan Reddy, V.; Sai Krishna, Pavuluri (International Journal of Engineering and Technology, 2018)
Artist finding is the errand of distinguishing the creator of a given test from an arrangement of suspects. The free worry of this errand is to characterize a fitting portrayal of test that catches the composition styles of creators. In this task, weka based machine learning instruments are utilized for distinguishing proof of creator for highlight extraction of reports spoke to utilizing variable size character n-grams. We wrote our own java program to extract the features like number of words, sentences etc. From, the poem which in turn fed as input to weka tool for the identification of author then after testing the input with all the algorithm all the accuracy rates are noted down to see which algorithm is given us the best accuracy rate. Now to find the author name for an anonymous poem the poem features are extracted using the java code and the output is taken in the java file given to the weka tool and tested with the algorithms and then the author name is given to the anonymous poems.Â Â